Dynamic Scheduling Algorithm With Task Execution Time Estimation Method In Cloud - Radwal, Babita Rani; Kumar, Sanjay (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we consider dynamic scheduling algorithm with task execution time estimation method in cloud which aims to satisfy the workflow deadline by consuming the figure of job performance time prospect and typical nonconformity to approximation real task finishing times. Existing workflow scheduling algorithms in the grid and cloud background concentrated on a number of QoS parameters such as cost, CPU time, makespan and dependability etc. An Effectual Load Balancing based on Resource Utilization is proposed and related algorithm is executed on CloudSim and its toolkit. The results show the effectiveness and decrease the renting cost of the proposed algorithm. The proposed algorithm improves efficiency and response time compared to delay based dynamic scheduling.